2017
DOI: 10.1051/e3sconf/20171700026
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining zeolites from slags and ashes from a waste combustion plant in an autoclave process

Abstract: Abstract. Waste combustion is associated with the generation of postprocessing solid products -waste such as slag and ash. One of the promising technologies in waste management and processing is the synthesis of zeolites and other materials exhibiting sorption properties. The aim of this study was to characterise and assess the physicochemical properties of the waste and the products synthesised from it. This paper presents the possibility of synthesis zeolites from the slag and ash from two waste combustion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Yukselen-Aksoy [11] found that zeolites are mechanically stable and are appropriate for use in landfill liner and embankment materials. Grela et al [12] showed that zeolite can also be received from waste materials such as fly ashes. The use of zeolite can reduce the unavoidable environmental issues associated with the production of cement such as CO 2 release and consumption of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Yukselen-Aksoy [11] found that zeolites are mechanically stable and are appropriate for use in landfill liner and embankment materials. Grela et al [12] showed that zeolite can also be received from waste materials such as fly ashes. The use of zeolite can reduce the unavoidable environmental issues associated with the production of cement such as CO 2 release and consumption of energy.…”
Section: Introductionmentioning
confidence: 99%